Adeno-associated virus 9 vector-mediated cardiac-selective expression of human secretory leukocyte protease inhibitor attenuates myocardial ischemia/reperfusion injury - Mongkolpathumrat, Podsawee; Nernpermpisooth, Nitirut; Kijtawornrat, Anusak; Pikwong, Faprathan; Chouyratchakarn, Wannapat; Yodsheewan, Rungrueang; Unajak, Sasimanas; Kumphune, Sarawut (Frontiers in Cardiovascular Medicine, 2022)
Protease enzymes contribute to initiation of cardiac remodeling and heart failure after myocardial ischemic/reperfusion (I/R) injury. Protease inhibitors attenuate protease activity and limit left ventricular dysfunction and remodeling. Previous studies showed the cardioprotective effect of secretory leukocyte protease inhibitor (SLPI) against I/R injury. However, overexpression of SLPI gene in cardiovascular diseases have only been investigated in an in vitro experiment. Here, cardiac selective expression of the human secretory leukocyte protease inhibitor (hSLPI) gene and its effect on I/R injury were investigated. Adeno-associated virus (AAV) serotype 9 carrying hSLPI under the control of cardiac selective expression promotor (cardiac troponin; cTn) was intravenously administered to Sprague-Dawley rats for 4 weeks prior to coronary artery ligation. Results showed that myocardial selective expression of hSLPI significantly reduced infarct size, cardiac troponin I (cTnI), creatine kinase-MB (CK-MB), and myoglobin levels that all served to improve cardiac function. Moreover, overexpression of hSLPI showed reduction in inflammatory cytokines, oxidatively modified -protein carbonyl (PC) content, and ischemic modified albumin (IMA), as well as necrosis and cardiac tissue degeneration. In conclusion, this is the first study to demonstrate cardiac selective gene delivery of hSLPI providing cardioprotection against myocardial I/R injury in an in vivo model.